Legal aspects of eco-coin, the new environmentally friendly virtual currency - Alvares-Garcia Júnior, Armando (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Environmental protection, a matter of considerable seriousness and relevance in various spheres, finds itself at the epicentre of a financial revolution. Recently, a novel cryptocurrency, dubbed “Eco-Coin”, has emerged with the aim of promoting sustainable trade and investment, becoming a phenomenon of great interest in some nations. However, this financial phenomenon poses a series of legal challenges that warrant thorough analysis. In this regard, our study proposes to examine the complex web of legal issues surrounding the Eco-Coin, and strives to shed light on its regulatory framework, the implications of its use, and other normative considerations that arise in relation to its implementation and operation.